Clinical outcomes of AngioJet rheolytic thrombectomy in the treatment of May–Thurner syndrome-related deep venous thrombosis. Issue 6 (June 2022) - Wei, Wen-Cheng; Hsin, Chun-Hsien; Yang, Hsuan-Tzu; Su, Ta-Wei; Su, I-Hao; Chu, Sung-Yu; Ko, Po-Jen; Yu, Sheng-Yueh; Lee, Chun-Hui
Objective: May–Thurner syndrome (MTS) is an anatomic stenotic variation associated with deep vein thrombosis (DVT) of the left leg. The classical DVT treatment strategy is medical treatment without thrombus removal. This study was performed to assess the clinical outcomes of the combination of AngioJet™ rheolytic thrombectomy and stenting for treatment of MTS-related DVT. Methods: We conducted a retrospective cohort study of patients treated for MTS-related DVT from January 2017 to June 2020 at a single institution. Results: Fourteen patients (nine women) underwent AngioJet™ rheolytic thrombectomy for MTS-related DVT during the study period. The median DVT onset time was 8 days (interquartile range (IQR), 3–21 days). The median procedure time was 130 minutes (IQR, 91–189 minutes), and the median hospital stay was 7 days (IQR, 5–26 days). One patient had a residual thrombus and occluded iliac stent and underwent adjuvant catheter-directed thrombolysis for revascularization. The primary patency rate for the iliac stent was 92.9% at 12 months. Conclusion: Concomitant AngioJet™ rheolytic thrombectomy and stenting of MTS-induced lesions may be beneficial for patients with MTS-related DVT.